Geronimo Stilton. Books 4-6 [compact disc, unabridged]. - Stilton, Geronimo (Geronimo Stilton, 2005)
Geronimo Stilton runs a newspaper, but his true passion is writing tales of adventure. Here in New Mouse City, the capital of Mouse Island, his books are all bestsellers! His stories are full of fun--tastier than Swiss cheese and tangier than extra-sharp cheddar. They are whisker-licking-good stories, and that's a promise! Here are three more of his adventures.